PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP PENINGKATAN HASIL BELAJAR EKONOMI PESERTA DIDIK - Pramudya, Yudha (Universitas Tanjungpura, 2023)
This research aims to determine the application of the flipped classroom learning model in improving the economic learning outcomes of students in class XI IPS I Islamic High School Bawari Pontianak. This research uses a quasi-experimental method on international cooperation material. In the learning process, researchers applied a learning model involving 25 students. Based on data analysis, it was concluded that: 1) The results of the research showed that the implementation of the flipped classroom learning model in class Pretest results/before students learn using the flipped classroom model 21.2. Meanwhile, the results of the posttest/after using the flipped classroom learning model were 76.4, so it can be stated that the flipped classroom learning model can improve student learning outcomes. 3) Based on the t-test, the pretest and posttest data show a significant effect of 0.000 Ë‚Î± 0.05 , which means that there are differences in learning outcomes before and after learning using the flipped classroom learning model. The effectiveness of the flipped classroom learning model has been proven to have a positive influence on student learning outcomes so that these results can be used as a reference for researchers or other teachers to be implemented and developed in their respective educational units.